Green Synthesis of Chitosan Nanoparticles Using Cinnamomum Cassia L. Hexane Bark Extract and Its Antibacterial Activity Against MDR Klebsiella Pneumoniae - Abbas, Zeyad S.; Jassim, Emad H.; Jasim, Hameed M. (Iraqi Journal of Science, 2026)
The biosynthesis of nanoparticle is suggested as an eco-friendly and economical alternative to both physical and chemical approaches. This study sought to assess the antibacterial with cytotoxic effects of Cinnamomum cassia L. oil extract (COE) and cinnamon oil extract/chitosan nanoparticles (COE/ChNPs) against MDR Klebsiella Pneumoniae and Mouse embryonic fibroblast cell line. Cinnamon active components such as alkaloids, glycosides, phenols, steroids, terpenes, saponins, tannins, and flavonoids were detected in hexane extract. Green synthesis of COE/ChNPs was achieved using the sol-gel technique, resulting in uniform, spherical, crystalline nanoparticles ranging from 40 to 96 nm. COE/ChNPs were characterized using UV-visible spectrophotometry, Transmission Electron Microscopic (TEM), and X-ray Diffraction (XRD) analyses. Results of the antibacterial activity of COE/ChNPs showed a significant effect against 12 MDR K. pneumoniae isolates from urinary tract infections compared with COE. The minimal inhibitory concentrations (MIC) of COE/ChNPs and COE were ranged from 0.18 to 0.71 µg/ml, and 750 to 2810µg/ml, respectively. The in vitro cytotoxic effect of biologically synthesized COE/ChNPs against mouse embryonic fibroblast cell lines was assessed. Results showed that there is a cytotoxic effect of COE/ChNPs inhibition of embryonic fibroblast cell lines growth in a concentration-dependent manner as determined using MTT assay.